Archeal Di-O-geranylgeranyl glyceryl phosphate synthase of a UbiA superfamily member provides insight into the multiple human diseases - Boral, Debjyoti; Rao, Vamkudoth Koteswara; Ramasamy, Sureshkumar (Protein and Peptide Letters, 2020)
One of the unique characteristic features of the domain archaea, are the lipids that form the hydrophobic core of their cell membrane. These membrane lipids are characterized by distinctive isoprenoid biochemistry and the building blocks are two core lipid structures, sn-2,3-diphytanyl glycerol diether (archaeol) and sn-2,3-dibiphytanyl diglycerol tetraether (caldarchaeol). Archaeol has two phytanyl chains (C-20 in a bilayer structure connected to the glycerol moiety by an ether bond. The enzyme involved in this bilayer formation is Di-O-Geranylgeranyl Glyceryl Phosphate Synthase (DGGGPS), which is a member of a very versatile superfamily of enzymes known as UbiA superfamily. Multiple sequence analysis of the typical members of the UbiA superfamily indicates that the majority of conserved residues are located around the central cavity of these enzymes. Interestingly few of these conserved residues in the human homologs are centrally implicated in several human diseases, on basis of the major mutations reported against these diseases in the earlier clinical studies. It remains to he investigated about the role of these conserved residues in the biochemistiy of these enzymes. The binding and active site of these enzymes found to be similar architecture but have different substrate affinities ranging from aromatic to linear compounds. So further investigation of UbiA superfamily may be translated to novel therapeutic and diagnostic application of these proteins in human disease management.
Keywords: Archeal lipids; biA superfamily; DGGGPS; genetic diseases; lipid synthesis; membrane protein